1995
DOI: 10.1093/jnci/87.6.417
|View full text |Cite
|
Sign up to set email alerts
|

Stage, Age, Comorbidity, and Direct Costs of Colon, Prostate, and Breast Cancer Care

Abstract: More needs to be done to explore the reasons and implications of age-related cost differences. Cost-effectiveness analyses of cancer control interventions that shift cancer stage distributions may need to consider both the age and comorbidity of the target populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
202
2
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 321 publications
(218 citation statements)
references
References 0 publications
12
202
2
2
Order By: Relevance
“…Although nearly half of stage IV patients did not receive initial treatment, these patients were more likely to have multiple hospitalizations compared to stage III, which likely was a factor in driving up costs. These results contrast with Taplin et al 7 in that we observed increases in health-care utilization and costs among both regional and distant stages relative to local. As in our study, PCa-related costs were defined as the net costs between PCa cases and a group of age-matched controls.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although nearly half of stage IV patients did not receive initial treatment, these patients were more likely to have multiple hospitalizations compared to stage III, which likely was a factor in driving up costs. These results contrast with Taplin et al 7 in that we observed increases in health-care utilization and costs among both regional and distant stages relative to local. As in our study, PCa-related costs were defined as the net costs between PCa cases and a group of age-matched controls.…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have been conducted that examine the effect of PCa stage on initial treatment costs with conflicting results. [7][8][9] The majority of costs related to PCa occur during the period of initial treatment. Both Taplin et al 7 and Penberthy et al 8 reported that initial PCa stage did not affect treatment costs whereas Penson et al 9 concluded that first-year costs do increase by stage particularly for patients treated with radical prostatectomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, many of the studies identified only examine costs for patients diagnosed with early stage PCa. [6][7][8] A few older studies 9,10 have examined costs in phases of care beyond initial treatment and have stratified estimates by cancer stage. However, these studies consider costs over earlier periods (1990-1991 9 and 1973-1991 10 ), which may be less relevant today given the changes in approach to PCa diagnosis and treatment that have occurred.…”
Section: Introductionmentioning
confidence: 99%
“…There is no evidence that the SEER-Medicare data are not reflective of national enrollment patterns in FFS and HMOs. Previous research has found that expense patterns generated from SEER-Medicare and HMO data are roughly consistent (9)(10)(11); no studies, however, have systematically examined how cancer-specific and longitudinal patterns of resource and service use and overall expense differ between HMOs and Medicare. Building on the work of the Cancer Research Network [CRN (12)(13)(14)], the Burden of Cancer study (BURDEN) has developed a multisite, multipayer database to support analyses extending and complementing the linked SEER-Medicare data.…”
Section: Measuring the Medical Cost Of Cancermentioning
confidence: 99%